Pengaruh Pemupukan Urea dan Nitrogen Slow Release Terhadap Pertumbuhan dan Kualitas Rumput Lapangan Golf - Nizar Nasrullah; Ni Ketut Wuri Tunggalini (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
The objectives of this study is to investigate the effect of (Urea) and Polymer Coated Urea (Slow Release N - Fertilizer) on the growth and quality of turf Bermuda grass (Cynodon dactylon var. Tifdwarf.) and to find the optimum rate. Treatments are urea and PCU rate at 4.5 g, 9.0g and 13.5 g N/m2/application, respectively. The experiment was arranged in Randomized Block design with 3 replications. Fertilizers were applied 6 times in every 2 locals. The result showed that in the end of the experiment, the higher values of grass height. number of shoots resiliance. Fresh and dry weight were obtained with PCU /3.5 g N/m2/application. The highest dosage of PCU resulted d the highest quality of turf grass.   Key words: Urea, Polymer Coated urea, Bermuda grass